Understanding biofeedback and its use in psychiatry - Swati Balkrishna Shelke; Rashmi V Singh (Annals of Indian Psychiatry, 2019)
Biofeedback is a technique which demonstrates the mind–body connection. It is training through which patients learn to exert voluntary control on involuntary body processes. Biofeedback can be helpful in the management of a wide variety of medical and psychiatric disorders. Among these are the anxiety-depression spectrum, psychosomatic disorders, chronic pain syndromes, as well as sleep disorders. Biofeedback is a good choice as main treatment and adjunct treatment in indicated disorders, if the patient prefers or when other treatment modalities are unsuccessful or contraindicated. The management of somatoform disorders is often a challenging task. Pharmacotherapy may not be effective or suitable in certain patients or situations, requiring different modes of interventions. In such cases, biofeedback can be effectively used. We, in this article, will review relevant research on the efficacy, mechanism of action, biofeedback training, planning of sessions, and clinical recommendations.